PENGARUH KARAKTERISTIK INDIVIDU, MANAJEMEN KONFLIK DAN KOMITMEN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN TONGAUNA KABUPATEN KONAWE - Suyono, Suyono; Abbas, Bakhtiar; Putera, Asrip (JIDE : Journal Of International Development Economics, 2024)
This study aims to determine and analyze the influence of individual characteristics, conflict management, and work commitment on employee performance at the Tongauna Subdistrict Office, Konawe Regency. The sample in this study consisted of all employees at the Tongauna Subdistrict Office, Konawe Regency, totaling 38 individuals. This study uses multiple linear regression analysis. The results of the study show that: (1) Individual characteristics, conflict management, and work commitment have a positive and significant effect on employee performance at the Tongauna Subdistrict Office, Konawe Regency. (2) Individual characteristics have a positive and significant effect on employee performance at the Tongauna Subdistrict Office, Konawe Regency. (3) Conflict management has a positive and significant effect on employee performance at the Tongauna Subdistrict Office, Konawe Regency. (4) Work commitment has a positive and significant effect on employee performance at the Tongauna Subdistrict Office, Konawe Regency.